DC-DC buck converter for triboelectric energy harvesting applications - Becermiş, Mustafa. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2019., 2019)
Energy harvesting applications are getting more popular day by day. Self suﬃcient circuits which do not require any supply, are more than a luxury for many situations. Usage of the battery can be expensive and not useful because of its large size and the impracticality that results from a need for replacing it in a certain period. Therefore, investments and research on energy harvesting applications are increasing. Energy can be harvested in many diﬀerent ways. One of them is triboelectric energy harvesting. With this technique, AC voltage is obtained from triboelectric nanogenerators but its open-circuit voltage can be high as 100V . Therefore, a system consisting of a bias-ﬂip rectiﬁer, DC-DC buck converter, and a switched capacitor converter is required to obtain usable energy at a low voltage level. This system gradually converts the harvested energy to lower levels. DC-DC buck converter delivers the 70V energy stored in the capacitor to the switched capacitor converter as 10V DC voltage. The goal is to deliver low input energy (10µ−30µJ) of which voltage is 70V to the output as eﬃciently as possible. In this thesis, an asynchronous buck converter operating in PFM mode is pro posed. The sub-blocks are designed to prevent a breakdown caused by high voltage. A speciﬁc start-up circuit is designed to start the operation of the proposed buck con verter. Each sub-block is shown with its layout and nearly 70% eﬃciency is obtained.
Keywords: Energy harvesting.; Electric current converters.